Digital twin-driven product design framework. Issue 12 (18th June 2019) - Tao, Fei; Sui, Fangyuan; Liu, Ang; Qi, Qinglin; Zhang, Meng; Song, Boyang; Guo, Zirong; Lu, Stephen C.-Y.; Nee, A. Y. C.
Abstract : With the advent of new generation information technologies in industry and product design, the big data-driven product design era has arrived. However, the big data-driven product design mainly places emphasis on the analysis of physical data rather than the virtual models, in other words, the convergence between product physical and virtual space is usually absent. Digital twin, a new emerging and fast growing technology which connects the physical and virtual world, has attracted much attention worldwide recently. This paper presents a new method for product design based on the digital twin approach. The development of product design is briefly introduced first. The framework of digital twin-driven product design (DTPD) is then proposed and analysed. A case is presented to illustrate the application of the proposed DTPD method.